Dynamics of Epiretinal Membrane Peeling under Perfluorocarbon Liquid Evaluated by Intraoperative OCT - Tomaso Caporossi; Stefano Maria Picardi; Gloria Gambini; Antonio Baldascino; Matteo Mario Carlà; Andrea Molle; Alessandra Scampoli; Lorenzo Governatori; Stanislao Rizzo (Life, 2023)
Background: The aim of this study is to provide intraoperative data demonstrating a significant difference in the membrane peeling dynamics performed under a perfluorocarbon (PFCL) bubble, compared to normal balanced saline solution (BSS). Methods: This is a prospective, interventional, single-center study on a series of 36 consecutive eyes of 36 patients affected by primary epiretinal membrane (ERM). Eighteen eyes underwent standard ERM peeling, while 18 eyes received a PFCL-assisted procedure. Intraoperative optical coherence tomography (iOCT) B-Scans were collected to evaluate the displacement angle (DA) between the underlying retinal plane and the flap of epiretinal tissue, along with the number of times the surgeon had to grab the flap during the intervention. Follow-up visits were carried out at postoperative week 1 and months 1, 3 and 6. Results: The mean DA was 164.8° ± 4.0 in the PFCL-assisted group and 119.7° ± 8.7 in the standard group, with a statistically significant difference between groups (p < 0.001). Moreover, we found a significant difference in the amount of ERM grabs between the two groups (7.2 ± 2.5 in the PFCL-assisted group vs. 10.3 ± 3.1 in the standard group, p = 0.005). The mean BCVA and metamorphopsia significantly improved in both groups (p < 0.05), with no significant intergroup difference at all follow-up visits. Similarly, CST significantly decreased in both groups, and final CST was similar between the two groups (p = 0.719). Overall, three eyes in the standard group developed postoperative dissociated optic nerve fiber layer (DONFL, 16.6%), compared to none of the PFCL-assisted group. Conclusion: We reported a statistically significant difference in the intraoperative peeling dynamics of the PFCL-assisted group, accounting for a decreased tendency in the tearing of the ERM flap and possibly reduced damage to the fiber layer, with equal effectiveness in improving visual function and foveal thickness.